2017
DOI: 10.1111/1440-1681.12742
|View full text |Cite
|
Sign up to set email alerts
|

Limb remote ischaemic postconditioning‐induced elevation of fibulin‐5 confers neuroprotection to rats with cerebral ischaemia/reperfusion injury: Activation of the AKT pathway

Abstract: Limb remote ischaemic postconditioning (RIPostC) is an effective and well-acknowledged treatment for brain ischaemia injury. The present study aimed to evaluate the role of fibulin-5 in the neuroprotection of RIPostC against cerebral ischaemia/reperfusion (I/R) injury in rats. The middle cerebral artery occlusion (MCAO) model was established in rats and then RIPostC was carried out by three cycles of 10 minutes occlusion/10 minutes release of the bilateral femoral artery at the beginning of the reperfusion. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Additional studies have revealed that RLIC activates the PI3K-pAkt pathway to induce cardioprotective effects, significantly upregulating the Bcl-2/Bax ratio by increasing p-Akt levels and the p-Akt/Akt ratio (44). Similar findings have been observed in models of MCAO (45), indicating that this process may be uniform across different diseases. CCCI due to large artery stenosis leads to decreases in p-Akt levels and the Bcl-2/Bax ratio in the cytoplasm and synapses of hippocampal neurons, suggesting that inhibition of Akt phosphorylation decreases the Bcl-2/Bax ratio and levels of neuronal apoptosis.…”
Section: Rlic May Regulate Various Pathophysiological Processes Assocsupporting
confidence: 84%
“…Additional studies have revealed that RLIC activates the PI3K-pAkt pathway to induce cardioprotective effects, significantly upregulating the Bcl-2/Bax ratio by increasing p-Akt levels and the p-Akt/Akt ratio (44). Similar findings have been observed in models of MCAO (45), indicating that this process may be uniform across different diseases. CCCI due to large artery stenosis leads to decreases in p-Akt levels and the Bcl-2/Bax ratio in the cytoplasm and synapses of hippocampal neurons, suggesting that inhibition of Akt phosphorylation decreases the Bcl-2/Bax ratio and levels of neuronal apoptosis.…”
Section: Rlic May Regulate Various Pathophysiological Processes Assocsupporting
confidence: 84%
“…In this process, the expression of Bcl-2 inhibits the expression of Bax, thus alleviating nerve cell apoptosis and achieving a protective effect. The mechanism of this process may be related to the Janus kinase 2 (JAK2)/signal transducer and activator of transcription-3 (STAT3) pathway (Cheng et al, 2014) and the PI3K/Akt pathway (Zhang et al, 2017a); the latter pathway has been extensively studied, and the former requires further testing.…”
Section: Overview Of Exosomesmentioning
confidence: 99%
“…The main pathophysiological changes in cerebral ischemia are the destruction of the blood-brain barrier and the entrance of macromolecular substances into the brain tissue, leading to cerebral edema and even bleeding [23]. Thrombolytic therapy allows the occluded blood vessels to be recanalized, and ischemic brain tissue is restored in time, but this restoration is accompanied by complex pathophysiological changes that aggravate cell damage and cell death and then induce cerebral ischemia/reperfusion injury [24].…”
Section: Discussionmentioning
confidence: 99%